Epigenetics in Adipose Tissue, Obesity, Weight Loss, and Diabetes(1)(2) - Martínez, J. Alfredo (American Society for Nutrition, 2014)
Given the role that diet and other environmental factors play in the development of obesity and type 2 diabetes, the implication of different epigenetic processes is being investigated. Although it is well known that external factors can cause cell type-dependent epigenetic changes, including DNA methylation, histone tail modifications, and chromatin remodeling, the regulation of these processes, the magnitude of the changes and the cell types in which they occur, the individuals more predisposed, and the more crucial stages of life remain to be elucidated. There is evidence that obese and diabetic people have a pattern of epigenetic marks different from nonobese and nondiabetic individuals. The main long-term goals in this field are the identification and understanding of the role of epigenetic marks that could be used as early predictors of metabolic risk and the development of drugs or diet-related treatments able to delay these epigenetic changes and even reverse them. But weight gain and insulin resistance/diabetes are influenced not only by epigenetic factors; different epigenetic biomarkers have also been identified as early predictors of weight loss and the maintenance of body weight after weight loss. The characterization of all the factors that are able to modify the epigenetic signatures and the determination of their real importance are hindered by the following factors: the magnitude of change produced by dietary and environmental factors is small and cumulative; there are great differences among cell types; and there are many factors involved, including age, with multiple interactions between them.